An Integrated ΔΣ A/D Architecture for Smart ISFET - Garnier-Fernández, D.; Serra-Graells, F.; Jiménez-Jorquera, C.; Baldi-Coll, A.; Arias de Fuentes, O. (Revista Cubana de Física, 2021)
In this paper, we present an architectural and electrical design of an integrated A/D converter configuration, based on ΔΣ modulation, for data acquisition from an ISFET (Ion Sensitive Field Effect Transistor) microsensor, applied to the development of a Smart ISFET. This A/D architecture in continuous-time, incorporates the microsensor as a component of the integrated circuit, together the required electronics for the automatic correction of the ISFET´s offset fulfilling the necessary requirements for the development of a portable device.